The Peripheral Blood Mononuclear Cell Count Is Associated With Bone Health in Elderly Men: A Cross-Sectional Population-Based Study. Issue 15 (April 2016) - Lin, Xianfeng; Yu, Hejun; Zhao, Chenchen; Qian, Yu; Hong, Dun; Huang, Kangmao; Mo, Jian; Qin, An; Fang, Xiangqian; Fan, Shunwu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The peripheral blood mononuclear cell (PBMC) count is a routinely used and meaningful index for infection and blood diseases. PBMCs may be closely related to osteoclasts and include osteoclast precursors; we examined the association between the PBMC count and bone health. This research included 2806 community men aged ≥50 years who underwent full health examinations from October 2007 through December 2011 in four medical centers. The PBMC count was significantly high among subjects with "at least osteopenia" compared with controls. In analysis of covariance adjusted for potential confounders, the bone mineral density (BMD) value and T-score had a significant decreasing trend across the quartiles of PBMC count. In univariate analysis, the PBMC count had a strong association with "at least osteopenia" (odds ratio [OR] = 2.520, 95% confidence interval [CI]: 1.397–4.547). After adjustment for confounding factors (multivariate analysis) from Model 1 to 4, PBMC count remained as an independent risk factor for "at least osteopenia" (OR = 2.481, 95% CI: 1.176–5.236). Moreover, after adjusting for all confounding variables, participants had a significantly high OR in the body mass index (BMI) <25 group (OR = 2.798, CI: 1.122–6.973; P = 0.027) and systolic blood pressure (SBP) <140 group (OR = 2.519, CI: 1.059–5.993; P = 0.037). In conclusion, the PBMC count is significantly associated with bone loss in elderly men and the exact mechanism requires further clarification.